2021
DOI: 10.1371/journal.pone.0260941
|View full text |Cite
|
Sign up to set email alerts
|

Mother-to-child transmission of HIV infection and its associated factors in the district of Bilene, Gaza Province—Mozambique

Abstract: Background Mother-to-child transmission of HIV infection is a significant problem in Mozambique. This study aims to determine the risk factors associated with mother-to-child transmission of HIV in rural Mozambique. Methods Retrospective case-control study in a rural area of Bilene District, on the coast of southern Mozambique, performed from January 2017 to June 2018. The analysis considered the clinical data of HIV exposed children with definitive HIV positive results and their respective infected mothers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 18 publications
(21 reference statements)
0
8
0
Order By: Relevance
“…Catchment area size and the involvement of multiple NGOs in the facility were associated with EID only (testing by 8 weeks of life). As hypothesized, increased staffing was associated with better performance in testing, but not with HIV transmission, as we suspect that individual patient-level factors continue to drive differential retention in care and ARV adherence, which in turn impacts viral suppression and the likelihood of vertical transmission [ 30 , 31 ]. Counterintuitively, stockouts of gloves were associated with higher likelihood to perform PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Catchment area size and the involvement of multiple NGOs in the facility were associated with EID only (testing by 8 weeks of life). As hypothesized, increased staffing was associated with better performance in testing, but not with HIV transmission, as we suspect that individual patient-level factors continue to drive differential retention in care and ARV adherence, which in turn impacts viral suppression and the likelihood of vertical transmission [ 30 , 31 ]. Counterintuitively, stockouts of gloves were associated with higher likelihood to perform PCR.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of MTCT is less than 2% if ART is started early in pregnant women living with HIV (WLHIV) and viral suppression is maintained [45]. It has been shown that a VL ≥1000 copies/mL is an independent risk factor for MTCT [46]. For high-risk WLHIV VL ≥1000 copies/mL, routine caesarean delivery reduces MTCT, whereas women in the later stages of gestation may not have VL results before delivery [47].…”
Section: Hiv Transmissionmentioning
confidence: 99%
“…Liu et al [10] describe that high maternal viral load, measured at delivery, as the strongest risk factor for both in utero and intrapartum transmission of HIV, and CD4+ T cell count, along with clinical stage of infection were also confirmed as significant predictors of transmission. The results of Osorio et al [11] showed that in rural Mozambique, the main predictor of MCTC was maternal viral load of 1000 copies/mL or more before delivery, as well as fewer than three antenatal care visits. Not being on cART by the first trimester and treatment non-adherence were also related to MTCT of HIV.…”
Section: Introductionmentioning
confidence: 99%